Synthesis of positive plasmas with known chromosomal abnormalities for validation of non-invasive prenatal screening - Qi, Zhongxia; Yu, Jingwei (Frontiers in Genetics, 2023)
Non-invasive prenatal screening (NIPS) is a DNA sequencing-based screening test for fetal aneuploidies and possibly other pathogenic genomic abnormalities, such as large deletions and duplications. Validation and quality assurance (QA) of this clinical test using plasmas with and without targeted chromosomal abnormalities from pregnant women as negative and positive controls are required. However, the positive plasma controls may not be available for many laboratories that are planning to establish NIPS. Limited synthetic positive plasmas are commercially available, but the types of abnormalities and the number/quantity of synthetic plasmas for each abnormality are insufficient to meet the minimal requirements for the initial validation. We report here a method of making synthetic positive plasmas by adding cell-free DNA (cfDNA) isolated from culture media of prenatal cells with chromosomal abnormalities to the plasmas from non-pregnant women. Thirty-eight positive plasmas with various chromosomal abnormalities, including autosomal and sex chromosomal aneuploidies, large deletions and duplications, were synthesized. The synthetic plasmas were characterized side-by-side with real positive plasmas from pregnant women and commercially available synthetic positive plasmas using the Illumina VeriSeq NIPT v2 system. All chromosomal abnormalities in the synthetic plasmas were correctly identified with the same testing sensitivity and specificity as in the real and commercial synthetic plasmas. The findings demonstrate that the synthetic positive plasmas are excellent alternatives of real positive plasmas for validation and QA of NIPS. The method described here is simple and straightforward, and can be readily used in clinical genetics laboratories with accessibility to prenatal cultures.